Women's Cardiac Rehabilitation Barriers: Results of the International Council of Cardiovascular Prevention and Rehabilitation's First Global Assessment - Ghisi, Gabriela Lima de Melo; Kim, Won-Seok; Cha, Seungwoo; Aljehani, Raghdah; Cruz, Mayara Moura Alves [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Pepera, Garyfallia; Liu, Xia; Xu, Zhimin; Maskhulia, Lela; Venturini, Elio; Chuang, Hung-Jui; et al. (Elsevier, 2023)
Background: Cardiac rehabilitation (CR) programs are underutilized globally, especially by women. In this study we investigated sex differences in CR barriers across all world regions, to our knowledge for the first time, the characteristics associated with greater barriers in women, and women's greatest barriers according to enrollment status. Methods: In this cross-sectional study, the English, Simplified Chinese, Arabic, Portuguese, or Korean versions of the Cardiac Rehabilitation Barriers Scale was administered to CR-indicated patients globally via Qualtrics from October 2021 to March 2023. Members of the International Council of Cardiovascular Prevention and Rehabilitation community facilitated participant recruitment. Mitigation strategies were provided and rated. Results: Participants were 2163 patients from 16 countries across all 6 World Health Organization regions; 916 (42.3%) were women. Women did not report significantly greater total barriers overall, but did in 2 regions (Americas, Western Pacific) and men in 1 (Eastern Mediterranean; all P < 0.001). Women's barriers were greatest in the Western Pacific (2.6 ± 0.4/5) and South East Asian (2.5 ± 0.9) regions (P < 0.001), with lack of CR awareness as the greatest barrier in both. Women who were unemployed reported significantly greater barriers than those not (P < 0.001). Among nonenrolled referred women, the greatest barriers were not knowing about CR, not being contacted by the program, cost, and finding exercise tiring or painful. Among enrolled women, the greatest barriers to session adherence were distance, transportation, and family responsibilities. Mitigation strategies were rated as very helpful (4.2 ± 0.7/5). Conclusions: CR barriers—men's and women's—vary significantly according to region, necessitating tailored approaches to mitigation. Efforts should be made to mitigate unemployed women's barriers in particular.